Patterns of river runoff change considering the size of the basin - Bagdžiunaitė-Litvinaitienė, Lina; Litvinaitis, Andrius; Šaulys, Valentinas (Journal of Environmental Engineering and Landscape Management, 2011)
Climatic change and fluctuations of river runoff are among the most urgent topics nowadays. It is important to analyse and establish tendencies for forecasting. The article deals with the reasons of runoff variation trends, i.e. river basins with different physical-geographical and meteorological conditions are analysed. In the research, statistical Mann-Kendall test and correlation coefficients were applied to assess the influence of precipitation amount variation on the variation of river discharges. The achieved results showed that the correlation links between a major river outflow (Neris) and precipitation were established only during autumn and winter seasons, however, the links were very weak (correlation coefficient of 0.4). The correlation between major river runoff and precipitation is also weak but can be observed during summer season as well. The highest correlation coefficients were established in rivers of average size. This proves that the smaller the river, the stronger is the reaction to local climatic factors.Article in English.Įvairaus baseino dydžio lietuvos upių nuotėkio kaita Santrauka. Klimato kaita ir upių nuotėkio svyravimai – viena iš aktualiausių nūdienos temų. Aptariama nuotėkio kaitos tendencijų priežastys, t. y. analizuojama upių baseinai, kurių skirtingos fizinės-geografinės bei meteorologinės sąlygos. Tyrimams taikyti statistikos Mann-Kendall testas bei koreliacijos koeficientai. Jais buvo įvertinta kritulių kiekio kaitos įtaka upių debitų kaitai. Gauti rezultatai parodė, kad labai didelės upės nuotėkio ir kritulių koreliacijos ryšiai nustatyti tik rudens ir žiemos sezonais, bet tai yra labai silpni ryšiai. Didelių upių nuotėkio ir kritulių tarpusavio sąsaja taip pat yra silpna, bet jau pastebima ir vasaros sezoną. Didžiausi koreliacijos koeficientai buvo vidutinio dydžio upių, ir tai įrodo, kad kuo mažesnė upė, tuo ryškesnė reakcija į lokalius klimato veiksnius.Reikšminiai žodžiai: debitas, klimato kaita,  Mann-Kendall testas, koreliacijos koeficientas.Изменение стока рек литвы разной крупностиРезюме. Изменение климата и колебания стока рек являются одним из наиболее актуальных вопросов сегодняшнего дня.В статье рассматриваются причины изменения стока, анализируются бассейны рек с разными физикогеографическими и метеорологическими условиями. При исследованиях использовался статистический тестМаннаКендалла и коэффициенты корреляции для учета влияния количества осадков на оценку изменения стокарек. Полученные результаты показали, что для очень крупных рек (Нерис) корреляционные связи стока и количества осадков установлены лишь в осеннезимний период, однако эта связь очень слаба (коэффициент корреляции0,4). Связь стока и количества осадков для меньших рек является слабой, однако она наблюдается и в летний период. Наибольший коэффициент корреляции зафиксирован для рек средней величины. Таким образом, установлено, что чем меньше река, тем резче реакция ее стока на локальные климатические действия.Ключевые слова: сток, изменение климата, осадки, тест Манна-Кендалла, коэффициент корреляции.